Pemberdayaan Kader Kesehatan dalam Pencegahan Kanker Payudara melalui Edukasi dan Pendampingan Praktik SADARI - Jafar, Sitti Rusdianah; Purnamawati, Dewi; Mas'adah, Mas'adah; A'Sentana, A'an Dwi; Zahrani, Azura; Ningrum, Amelia Pebria; Pratama, I Nyoman Wirya (Jurnal Gema Ngabdi, 2025)
Breast cancer is a leading cause of cancer death among women in Indonesia. Early detection through breast self-examination (BSE) is a crucial step in reducing delays in diagnosis. However, the knowledge and skills of healthcare workers in rural areas remain limited. This community service activity aims to improve the knowledge, attitudes, and skills of healthcare workers regarding early breast cancer detection through education and mentoring in BSE practices in Batukumbung Village, Lingsar District, West Lombok Regency. The implementation method included preparation, education, BSE practice training, and mentoring. Evaluation was conducted through pre- and post-tests. Results showed an increase in respondents' knowledge from sufficient (75%) to good (95%) after the education. Positive attitudes toward the importance of early detection also increased from 70% to 92%. Furthermore, skills in performing BSE practices improved, from no respondents able to perform the steps correctly at the initial assessment to 60% at the final assessment. This activity has proven effective in increasing the capacity of healthcare workers in early breast cancer detection and is expected to contribute to prevention efforts at the community level.